Identification of KRT16 and ANXA10 as cell cycle regulation genes for lung adenocarcinoma based on self-transcriptome sequencing of surgical samples and TCGA public data mining - Wen-jian Liu; Jia-pan Shen; Ren-quan Zhang; Xiao-yun Fan (Discover Oncology)
Abstract Aim This study aimed to identify the genes associated with the development of lung adenocarcinoma (LUAD) and potential therapeutic targets. Methods Differentially expressed genes (DEGs) were identified by self-transcriptome sequencing of tumor tissues and paracancerous tissues resected during surgery and combined with The Cancer Genome Atlas (TCGA) data to screen for the genes associated with LUAD prognosis. The expression was validated at mRNA and protein levels, and the gene knockdown was used to examine the impact and underlying mechanisms on lung cancer cells. Results A total of 227 DEGs were identified by transcriptome sequencing, and the 20 DEGs with the most significant differences were used for co-analysis with TCGA data. The findings suggested that KRT16 and ANXA10 might have an important role in the development of LUAD after validating the mRNA and protein expression levels at the cellular level. The knockdown of KRT16 and ANXA10 inhibited the proliferation of lung cancer cells, and the cell cycle was blocked in the G1 phase. The expression of the G1/S–phase cell cycle checkpoint–related proteins cyclin D1 and cyclin E was inhibited by KRT16 and ANXA10 knockdown, respectively. The tumor formation ability decreased after KRT16 or ANXA10 knockdown in vivo. Conclusions KRT16 and ANXA10 are potential genes regulating the development of LUAD. Also, they may be potential targets for the targeted therapy of LUAD by inhibiting the proliferation of lung cancer cells and blocking the cell cycle by affecting key protein expression levels at cell cycle checkpoints.